2013
DOI: 10.1073/pnas.1219809110
|View full text |Cite
|
Sign up to set email alerts
|

Candidate phylum TM6 genome recovered from a hospital sink biofilm provides genomic insights into this uncultivated phylum

Abstract: The "dark matter of life" describes microbes and even entire divisions of bacterial phyla that have evaded cultivation and have yet to be sequenced. We present a genome from the globally distributed but elusive candidate phylum TM6 and uncover its metabolic potential. TM6 was detected in a biofilm from a sink drain within a hospital restroom by analyzing cells using a highly automated single-cell genomics platform. We developed an approach for increasing throughput and effectively improving the likelihood of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
166
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 76 publications
2
166
0
1
Order By: Relevance
“…Features expected in symbionts include small genome size, AT bias and loss of biosynthetic pathways 29,30 . Recently, McLean et al 31 reported a similarly small genome for a member of the TM6 CP and suggested that the organism is a symbiont, and Gong et al 32 showed that an OD1 bacterium occurs intracellularly in a protist.…”
Section: Discussionmentioning
confidence: 99%
“…Features expected in symbionts include small genome size, AT bias and loss of biosynthetic pathways 29,30 . Recently, McLean et al 31 reported a similarly small genome for a member of the TM6 CP and suggested that the organism is a symbiont, and Gong et al 32 showed that an OD1 bacterium occurs intracellularly in a protist.…”
Section: Discussionmentioning
confidence: 99%
“…XH001 alone and XH001/TM7x coculture were used to infect J2 BMM cells, and quantitative PCR was conducted to monitor their TNF-α induction. Furthermore, XH001/ TM7x cocultures grown in the SHI medium were shotgun-sequenced and assembled using SPAdes, followed by contig binning and annotation as described by McLean et al (31) to assemble the genomes independently. Genome completeness for all TM7x and published TM7 assemblies was estimated based on 111 universal, single-copy genes.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, it is plausible that Cand. IA might also employ a modified electron transport chain, similar to that recently suggested for candidate division TM6 (McLean et al, 2013). The chain will involve disulfide bond oxidoreductase D (DsbD), a thioredoxin-disulfide (NADPH) reductase (EC.…”
Section: General Features Of 'Diapherotrites' Genomesmentioning
confidence: 99%